Cancer chemotherapy: insights into cellular and tumor microenvironmental mechanisms of action - Tilsed, Caitlin M.; Fisher, Scott A.; Nowak, Anna K.; Lake, Richard A.; Lesterhuis, W. Joost (Frontiers in Oncology, 2022)
Chemotherapy has historically been the mainstay of cancer treatment, but our understanding of what drives a successful therapeutic response remains limited. The diverse response of cancer patients to chemotherapy has been attributed principally to differences in the proliferation rate of the tumor cells, but there is actually very little experimental data supporting this hypothesis. Instead, other mechanisms at the cellular level and the composition of the tumor microenvironment appear to drive chemotherapy sensitivity. In particular, the immune system is a critical determinant of chemotherapy response with the depletion or knock-out of key immune cell populations or immunological mediators completely abrogating the benefits of chemotherapy in pre-clinical models. In this perspective, we review the literature regarding the known mechanisms of action of cytotoxic chemotherapy agents and the determinants of response to chemotherapy from the level of individual cells to the composition of the tumor microenvironment. We then summarise current work toward the development of dynamic biomarkers for response and propose a model for a chemotherapy sensitive tumor microenvironment.